Pattern of Dysglycaemia and Its Associated Risk Factors amongst Civil Servants in an Urban Community in Southern Nigeria - Osaro Enogie Ejenobo; Oluwatoyin A. Ohenhen; Noruwa Patience Ekhator; Adrian Aigbe; Andrew Efosa Edo (Nigerian Journal of Medicine)
Background: The global prevalence of diabetes mellitus (DM) is estimated to be 10.5% and majority of those affected are in the economically productive age group. A significant proportion of civil servants are considered at high risk for development of diabetes because of the sedentary nature of their job. Objectives: This study aimed to determine the prevalence and associated risk factors for dysglycaemia amongst civil servants in an urban community. Methods: This study was a cross-sectional study with a total of 84 participants. Data on the sociodemographic, medical history, family and social history of the participants were collected using a participant-filled questionnaire. Anthropometric measurements (height, weight, waist circumference and hip circumference), blood pressure and fasting plasma glucose levels were obtained. Impaired fasting glucose (IFG) and DM were defined using the World Health Organisation criteria. Results: The mean (standard deviation) age of the participants was 38 (9.7) years. The prevalence of IFG and diabetes was 14.3% and 7.1%, respectively. The overall prevalence of dysglycaemia was 21%. There was no significant difference in prevalence of dysglycaemia amongst males and females. Hypertension and obesity were present in 29.8% and 13.1% of participants, respectively. The risk factors significantly associated with dysglycaemia were hypertension and a positive family history of DM. Conclusion: This study demonstrated a high prevalence of dysglycaemia in the study population. There is a need for targeted interventional programmes aimed at reducing the risk factors for dysglycaemia as well as providing regular screening for civil servants.